Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

Aligning green spaces with human activity: uncovering opportunity-realization mismatches in urban green exposure - Yicheng Zheng; Tao Lin; Nicholas A.S. Hamm; Yuan Chen; Tongyu Zhou; Xiangzhong Guo; Hongkai Geng; Matthew Ng; Hoon Han; Christopher Pettit; Yong-Guan Zhu (Landscape and Urban Planning, 2026)

Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

Dielectrically tuned core-shell microwave-responsive sorbents for high-efficiency direct air capture - Wenjing Li; Mingxing Zhou; Xiaoyan Ji; Yunxia Wen; Han Lin; Xiaohua Lu; Xinwei Zhang; Xiwen Zhang; Tuo Ji; Shuandi Hou; Jiahua Zhu (Chemical Engineering Journal, 2026)

General applicability for developing interfacial regulation materials: An artificial-intelligence-driven approach based on non-covalent interactions - Changqing He; Yang Xue; Huimin Zhou; Xincheng Zhang; Xueqian Liu; Lin He; Hong Sui; Zhenghe Xu; You Han (Chemical Engineering Journal, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Biodegradable mulching and nitrogen fertilization differentially affect AM fungal community structure and functioning in a semi-arid maize agroecosystem - Lin Mao; Yae Luo; Jingru Yan; Huan Jin; Dachuan Liu; Jiayao Han; Yali Zhang; Zhou Fang; He Mao (Mycorrhiza, 2026)

TEC2Ne: a physics-informed deep learning framework for reconstructing ionospheric electron density profiles from global TEC maps - Chenghao Li; Hanxian Fang; Chao Xiao; Die Duan; Yang Lin; Hongtao Huang; Ganming Ren; Han Wu; Chuyue Zhou; Haiyang Zheng; Xuhui Shen; Xiaoqun Cao (GPS Solutions, 2026)

Agricultural management shapes soil multitrophic communities and biodiversity-ecosystem function relationships in a dryland agroecosystem - Jiayao Han; Yali Zhang; Hao Xi; Lin Mao; Zhou Fang; Chenyu Li; Yongjun Liu (Agriculture, Ecosystems & Environment, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

Rainfall-driven electron acceptors loss constrain natural attenuation of petroleum hydrocarbons and development of a rainfall-responsive biostimulation strategy - Boyan Lai; Zichen Lin; Han Cui; Chaofan Zhang; Dandan Zhou (Journal of Hazardous Materials, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

In situ macrophage reprogramming via micropatch engineering for safe and effective antitumor adoptive cell therapy - Yongkang Xu; Lei Cao; Yuyan Zhou; Wenhao Li; Han Lin; Yuan Yong; Jianlin Shi; Wencheng Wu (Science Bulletin, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

New insight into mercury sources and trophic transfer in the Bohai Sea food web using carbon, nitrogen, and mercury stable isotopes - Xiaowei Qiao; Shuangxu Zhou; Lin Yang; Hua Guo; Tao Yang; Wenjing Li; Zhuo Ma; Deming Han; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Fish diversity and community turnover across protection zones in multiuse marine protected areas - Xu Zeng; Cong Zeng; Yongfeng Zhou; Yue Liu; Zheying Lin; Jihao Peng; Yihui Jiang; Han Dong; Guodong Li; Shuangzhao Li; Hengyu Li; Ling Cao (Conservation Biology, 2026)
Multiuse marine protected areas (MMPAs) with varying levels of protection in different zones are increasingly being adopted to balance conservation and socioeconomic goals. However, the effect of these zone‐based strategies on fish diversity is not well understood. We used environmental DNA surveys across zones with different protection levels (fully protected, highly protected, and lightly protected) in three typical Chinese MMPAs, while controlling for environmental factors and human activities, to examine fish species composition and richness among zones. Contrary to expectations, sites with high levels of protection had lower fish species richness than sites with lower levels of protection. Turnover in community composition between fully protected and less protected zones was 88.4% and accounted for 96.4% of pairwise dissimilarities. Rather than diminishing the importance of high‐level protection, our results showed that a tiered zoning approach can sustain fish species richness and limit biotic homogenization. Our results challenge the assumption that strict protection universally leads to high species richness and demonstrate that nuanced multilevel protection zoning may be more effective at preserving marine biodiversity and ecosystem functions at broader spatial scales.

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Expanded coverage of N-acyl amino acids using one-pot micro synthesis-chemical derivatization-LC-MS strategy: A key to bioactive compounds analysis in fermented soybean - Jie Han; Yujie Li; Lanjia Ao; Li Zhang; Tingting Zhou; Na Li; Jian-Lin Wu (Food Chemistry, 2026)

Collaborative supply chain management decision-making considering CCUS technology under carbon trading mechanisms - Han Song; Junru Ye; Na Zhou; Jinchai Lin (Environment, Development and Sustainability, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Three-dimensional green quantity (3DGQ) mapping and integrated 2D–3D assessment reveal hidden urban green deficits and inequities - Shoubang Huang; Kai Zhou; Jingyi Han; Haochun Hu; Shiyang Zhang; Qing Lin; Xiangrong Wang (Journal of Environmental Management, 2026)

Nb5+ pre-intercalation synergistically regulates layered vanadates for high-performance aqueous Zn-ion batteries - Shenglin Zhong; Denglian Chen; Xiang Hu; Han Lin; Menghui Mu; Zhenhai Wen; Jiangcong Zhou (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Quantitative research from the perspective of mathematical and physical crop science: a review of phenotyping, mechanics, and modeling - Zaibin Wang; Qingting Liu; Yan Zhang; Xueting Han; Tao Wu; Qing Zhou; Zhenghe Luo; Xiaojuan Lin (Plant Molecular Biology, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Two Novel Peniphenone Derivatives with Distinct Stereoconfigurations from Ascidian-Derived Fungus Diaporthe sp. SYSU-MS4722 and Their Anti-Fibrotic Activities - Shuya Ren; Yanhong Han; Yan Yan; Yuran Zhou; Siwen Yuan; Junjie Chen; Heng Guo; Zhenjian Lin; Qifeng Lin; Senhua Chen; Lan Liu; Yongkang Qiao; et al. (Journal of Ocean University of China, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Click Chemistry-Based Quantification of Extracellular Matrix Turnover for Drug Screening and Regenerative Medicine - Annie Porter; Songshan Fan; Ying Peng; Mengxi Lv; Yilu Zhou; Abdulaziz Alanazi; Lin Han; Liyun Wang; X. Lucas Lu (Annals of Biomedical Engineering, 2026)
Purpose To develop and validate a bioorthogonal labeling approach for quantifying ECM remodeling in living cell and tissue culture systems. Methods Strain-promoted azide-alkyne (SPAAC) reactions, or copper-free click chemistry, were used to fluorescently label newly synthesized glycan and protein matrix components. ECM synthesis and degradation was quantified in cartilage explants, human mesenchymal stem cells, and SKBR3 breast cancer cells under various external stimuli, including inflammation, mechanical stimulus, and drug treatment. Results The click chemistry method reliable quantified ECM turnover across platforms. It detected reduced glycan and protein synthesis after 24-hour inflammatory challenge and enabled longitudinal tracking of ECM degradation in cartilage explants. The technique demonstrated high sensitivity, measuring increased ECM deposition by ~ 10,000 human mesenchymal stem cells in 12-hour intervals and substrate stiffness-dependent synthesis by SKBR3 cells. Additionally, the approach supported osteoarthritis drug screening by identifying compounds that mitigated inflammation-induced ECM degradation. Conclusion Compared to traditional biochemical or histological assays, the click chemistry-based technique provides higher sensitivity, reduced sample requirements, and improved temporal resolution for quantifying ECM turnover. Its versatility enables broad application in tissue engineering, regenerative medicine, disease modeling, and high-throughput drug evaluation.

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Root traits determine the effects of organic amendments on soil aggregate organic carbon by regulating soil microbial multitrophic networks - Changdong HAN; Lin CHEN; Zhongjun JIA; Hongtao ZOU; Ling MA; Jingwang LI; Congzhi ZHANG; Guixiang ZHOU; Donghao MA; Jiabao ZHANG (Pedosphere, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Green and scalable design of plant-based MoS2-OA Pickering nanofluids for simultaneous friction reduction and heat dissipation in sustainable metalworking - Wei Wang; Deping Xia; Xin Wang; Hualin Lin; Jingzhou Liu; Shuai Huang; Mingan Zhou; Bin Dai; Sheng Han (Journal of Environmental Chemical Engineering, 2026)

Active faulting and crustal deformation along the East Sunda-Banda Arc: Implications for Regional Geohazards - Xiaodong Yang; Xiwu Luan; Liangyu Zhu; Xinze Han; Zhiwen Zhang; Zhiyuan Zhou; Jian Lin; Liming Wang (Global and Planetary Change, 2026)

From digestion to delivery: the gastrointestinal fate and functional duality of goat milk-derived extracellular vesicles - Chunping Chen; Cong Zheng; Fangcheng Hu; Yue Li; Xingyuan Liu; Wenxu Zhou; Baolong Liu; Lin Han; Caian He; Min Wang (Food Chemistry, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Integrated Analysis of mRNA-seq and miRNA-seq Reveal the Dynamics of the Gonadal Differentiation of Procypris Mera - Zhenling Ke; Weijun Wu; Zhe Li; Yusen Li; Yaoquan Han; Jun Shi; Lilong Chen; Kangqi Zhou; Dapeng Wang; Yong Lin; Min Li; Hua Ye (Marine Biotechnology, 2026)

Highly effective masculinization of mandarin fish (Siniperca chuatsi) using Etonogestrel: A practical method for aquaculture and transcriptomic mechanism elucidation - Jiangwei Zhou; Simin Zhong; Shengyue Lin; Shuzheng Ye; Dingxian Chen; Chong Han; Qiang Li (Aquaculture, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Multi-omics analysis reveals AaaaNAT1 as a critical regulator of physiological homeostasis in Aedes aegypti - Xue Gong; Zhinan Lin; Yanjiao Zhou; Dingfeng Duan; Qian Han; Chenghong Liao (Journal of Insect Physiology, 2026)

Interactive effects of irrigation and planting density on photosynthetic performance and yield of winter wheat - Muhammad Fraz Ali; Liijuan Ma; Wanrui Han; Yang Zhou; Shengnan Wang; Xiang Lin; Dong Wang (Field Crops Research, 2026)

An advanced multifunctional strategy - enabled triboelectric nanogenerator for efficient wind-energy harvesting - Bin Wang; Yan Gu; Yan Zhou; Yamei Liu; Ning Huang; Guangze Du; Xinyang Liu; Lingling Han; Huibo Zhao; Zhen Wang; Yingao Xue; Jieqiong Lin (Chemical Engineering Journal, 2026)

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Bio-inspired rigid-Soft interaction for robust picking underwater - Shuqiao Zhong; Wanghongjie Qiu; Xudong Han; Chaoyang Song; Zhiyuan Zhou; Fang Wan; Jian Lin (Ocean Engineering, 2026)

Lake expansion enhances inorganic and organic carbon sinks in sediments of lake Qinghai, Tibetan Plateau - Xianqiang Meng; Han Zhou; Qi Lin; Xianming Zhang; Li Huo; Jiayi Li; Lingkai Meng; Zhenyu Ni; Enlou Zhang (Journal of Environmental Management, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Shen-Ling-Bai-Zhu-San alleviates ulcerative colitis by enhancing mitophagy via the Nrf2/PINK1/Parkin pathway - Huan Wang; Jian Han; Lin Li; Yan Li; Jun Yang; Wangzhong Qiu; Liuhua Yao; Jianjun Zhou (Journal of Molecular Histology, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

Experimental study of floating‐ice motion response and wave energy attenuation in an omnidirectional wave field - Yanzhuo Xue; Wangyuan Zhao; Chunhui Wang; Fenglei Han; Xiao Peng; Zeyu Zhou; Qing Chang; Qi Lin; Yuliang Wu (Ocean Engineering, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Confinement engineering of Co@C nanocages in 3D g-C3N4 scaffolds boosts photothermal CO2-to-fuel conversion - Yanan Wang; Jingjie Li; Rui Zhang; Tingting Xu; Chenlu Li; Jie Ma; Han Li; Liwei Lin; Song Xu; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Dry alkali-ball milling for high-solid conversion of biomass to sugar and ethanol: Comparison with conventional ball milling - Kaili Ding; Hao Lin; Xueli Chen; Xiwen Jia; Suan Shi; Xiaojun Guo; Ling Zhou; Lujia Han; Weihua Xiao (Fuel, 2025)

Exosome-like nanovesicles (EVNs): A comprehensive overview of their isolation, characterization and biological applications - Haiyu Wu; Pan Gao; Wenxu Zhou; Chunping Chen; Min Wang; Lin Han (Food Chemistry, 2025)

Efficient preparation of large-area anisotropic graphite films with high thermal conductivity and excellent electromagnetic shielding performance - Zhihong Han; Mingyi Tan; Daming Chen; Wenzheng Zhang; Zhipeng Lin; Jiahui Zhou; Yuhao Fang; Shengze Zhang; Qihong Wei; Xinghong Zhang; Wenbo Han (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

β-Lapachone sensitizes glioblastoma to Temozolomide by inhibiting NF-κB signaling - Chunhua Quan; Ying Liu; Yuan Gao; Houkun Zhou; Haiyan Quan; Anna Han; Xiaodan Lu; Zhenhua Lin (Functional & Integrative Genomics, 2025)

Can delivery riders act as informal guardians in crime prevention? - Shuli Zhou; Lin Liu; Han Yue; Kaiyin Yang; Jianjun Li; Guangwen Song (Applied Geography, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Deformation and Seepage Characteristics of Gassy Coal Subjected to Cyclic Loading–Unloading of Pore Pressure - Shugang Li; Chongzhi Wang; Bin Zhou; Haiqing Shuang; Haifei Lin; Shoujian Peng; Biao Hu; Han Yang; Hang Liu (Natural Resources Research, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Isolation and characterization of Pseudomonas sp. QX11 with high-efficiency aerobic denitrification for eutrophication control in aquaculture - Shanrui Shen; Yiyi Zhou; Hongli Cheng; Han Qian; Jun Wen; Chunmei Lin; Xiaofang Lai (Science of The Total Environment, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

In-situ construction of BiOBr/UiO-66(Zr/Ce) S-scheme heterojunction for efficient selective photocatalytic CO2 reduction to CO - Mengting Shen; Ling Wang; Man Zhou; Liwei Lin; Han Li; Yanan Wang; Song Xu; Zhongyu Li (Fuel, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Multifunctional Cu-engineered NH2-MIL-125Ti@ZnIn2S4 heterojunction with dual-channel H2O2 activation for ultrafast water-mediated Cr(VI) photoreduction - Guangyuan Chen; Wei Han; Chenyang Lin; Yubao Li; Shijian Zhou; Yan Kong (Chemical Engineering Journal, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

Multi-level resource utilization of food-grade nanomaterials from brewing residues: Synergistic polyphenol-pullulan membranes for litchi preservation - Congyu Lin; Peiqi Lu; Peihang Li; Zhimin Zhang; Jingqiu Ma; Yunfei Hou; Xiao Han; Zhongwei Ji; Zhilei Zhou; Dawei Li; Jian Mao (Chemical Engineering Journal, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Microbiological mechanisms of lignin- and humus-derived small molecule addition promoting straw conversion into soil organic matter in a sodic soil - Jingwang LI; Lin CHEN; Fengxia YUE; Congzhi ZHANG; Donghao MA; Guixiang ZHOU; Jiangli WANG; Changdong HAN; Biao FENG; Jiabao ZHANG (Pedosphere, 2025)

Harmonizing stakeholder interests in urban renewal: A novel planning approach using explainable machine learning and spatial optimization - Chuan Lin; Yilun Liu; Zhongyou Yuan; Hongmei Wang; Guang Li; Zegen Zhou; Han Wang; Xinyue An (Land Use Policy, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Cobalt-modification on UiO-bpydc MOF facilitates ligand-to-metal charge transfer for superior visible-light photocatalytic degradation of refractory fluoroquinolone antibiotics - Kaichun Lin; Jingjun Qin; Zhang Liu; Weicheng Xu; Meng Li; Yuanzhi Zheng; Wei Han; Guangying Zhou; Jianzhang Fang; Zhanqiang Fang; Feng Peng; King Lun Yeung (Environmental Research, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Organic amendments with low C/N ratios enhanced the deposition of crop root exudates into stable soil organic carbon in a sodic soil - Jingwang Li; Lin Chen; Congzhi Zhang; Changdong Han; Biao Feng; Donghao Ma; Guixiang Zhou; Jiabao Zhang (Plant and Soil, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Enhancing growth, pigment composition, polysaccharides, fatty and amino acid content in Ulva prolifera by manipulating temperature, light intensity, and photoperiod - Xuan Zhou; Mingzi Lin; Jianan Jiang; Shenyuan Liang; Han Xu; Wenrong Zhu; Nianjun Xu; Yahe Li (Aquaculture, 2025)

Can urban three-dimensional compact form reduce building operational carbon emissions? New evidence from a prototypical coastal city - Han Yan; Mengran Zhou; Kai Wang; Xian Wu; Tao Lin; Guoqin Zhang; Yongxin Liu; Hong Ye (Sustainable Cities and Society, 2025)

Performance of recycled aggregate concrete-filled high-strength steel tubular members under combined compression-bending-torsion - Zhi-Cheng Yang; Lin-Hai Han; Hua-Yang Zhao; Xiang-Yu Zhou (Engineering Structures, 2025)

Drying–rewetting cycles determine maize growth by shifting microbial community assembly and coexistence patterns - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Plant and Soil, 2025)

The impact of changing ambient population composition on crime during COVID-19 lockdowns - Xin Gu; Lin Liu; Su Yeon Han; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Applied Geography, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Lacticaseibacillus rhamnosus CP-1 mitigates LPS-induced acute lung injury in mice via TLR/NF-κB pathway and gut microbiota modulation - Jieqiong Lin; Zhonghua Wang; Jiaojiao Han; Jun Zhou (Food Bioscience, 2025)

Here comes the sun: integration of light, temperature, and auxin during herbaceous plant grafting - Ruiduo Han; Rui Lin; Yanhong Zhou; Hannah Rae Thomas (Planta, 2025)

Observer-based robust preview control for tracking low Earth orbit targets of a 2.5-meter optical telescope with wind disturbance - Jueqi Lin; Weirui Chen; Zheng Wang; Xiaojun Zhou; Yu Han (Advances in Space Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Faraday cage-type photocurrent polarity switching photoelectrochemical sensing platform for highly selective and sensitive detection of Vibrio parahaemolyticus - Qingqing Zhang; Tingting Zhai; Yuxin Guo; Yifan Weng; Nan Zhou; Han Lin; Hao Tan; Kangning Lu; Yiyi Zhou (Food Chemistry, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Long-term conservation tillage changes the diversity, assembly and network stability of soil diazotrophic community - Ling MA; Guixiang ZHOU; Jiabao ZHANG; Zhongjun JIA; Hongtao ZOU; Lin CHEN; Congzhi ZHANG; Donghao MA; Changdong HAN (Pedosphere, 2025)

Organic amendments enhance rhizosphere carbon stabilization in macroaggregates of saline-sodic soils by regulating keystone microbial clusters - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Congzhi Zhang; Guixiang Zhou; Donghao Ma; Jiabao Zhang (Journal of Environmental Management, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Development of a Mixotrophic Strategy for Efficient Cultivation of a Coccolithophore, Chrysotila roscoffensis - Luyao Zhang; Zhichao He; Yan Sun; Jian Li; Pengfei Cheng; Nicolas Spiros Agathos; Chengxu Zhou; Lin Zhang; Jichang Han (Journal of Ocean University of China, 2025)

Enhancing hexavalent chromium stable reduction via sodium alginate encapsulation of newly isolated fungal and bacterial consortia - Obey Kudakwashe Zveushe; Jackson Nkoh Nkoh; Víctor Resco de Dios; Tendai Terence Manjoro; Fidèle Suanon; Hengxing Zhang; Wenfang Chen; Lin Lin; Lei Zhou; Wei Zhang; Frank Sesu; Jin Li; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Three-Dimensional Lattice Modeling of Interaction Behavior Between Hydraulic Fractures and Natural Fractures with Varied Morphologies in Hot Dry Rock - Song Wang; Luqing Zhang; Lin Cong; Jian Zhou; Duoxing Yang; Xiufeng Zhang; Zhenhua Han (Rock Mechanics and Rock Engineering, 2025)

Conservation tillage regulates the influence of drought on multitrophic network complexity and improves soil multifunctionality - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Applied Soil Ecology, 2025)

Research on LSTM-PPO Obstacle Avoidance Algorithm and Training Environment for Unmanned Surface Vehicles - Wangbin Luo; Xiang Wang; Fang Han; Zhiguo Zhou; Junyu Cai; Lin Zeng; Hong Chen; Jiawei Chen; Xuehua Zhou (Journal of Marine Science and Engineering, 2025)
The current unmanned surface vehicle (USV) intelligent obstacle avoidance algorithm based on deep reinforcement learning usually adopts the mass point model to train in an ideal environment. However, in actual navigation, due to the influence of the ship model and the water surface environment, the training set is triggered. The reward function does not match the actual situation, resulting in a poor obstacle avoidance effect. In response to the above problems, this paper proposes a long and short memory network-proximal strategy optimization (LSTM-PPO) intelligent obstacle avoidance algorithm for non-particle models in non-ideal environments, and designs a corresponding deep reinforcement learning training environment. We integrate the motion characteristics of the unmanned boat and the influencing factors of the surface environment, based on the curiosity-driven set reward function, to improve its autonomous obstacle avoidance ability, combined with the LSTM network to identify and save obstacle information to improve the adaptability to the unknown environment; virtual simulation is performed in Unity. The engine builds a USV physical model and a refined water deep reinforcement learning training environment including a variety of obstacle models. The experimental results demonstrate that the LSTM-PPO algorithm exhibits an effective and rational obstacle avoidance effect, with a success rate of 86.7%, an average path length of 198.52 m, and a convergence time of 1.5 h. A comparison with the performance of three other deep reinforcement learning algorithms reveals that the LSTM-PPO algorithm exhibits a 21.5% reduction in average convergence time, an 18.5% reduction in average path length, and an approximately 20% enhancement in the success rate of obstacle avoidance in complex environments. These results indicate that the LSTM-PPO algorithm can effectively enhance the search efficiency and optimize the path planning in obstacle avoidance for unmanned boats, rendering it more rational.

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

In-situ forming flame-retardant gel polymer electrolyte through Ritter reaction: An innovative strategy for enhancing the safety of lithium metal battery - Si-Xin Jia; Tian-Qi Xiang; Zi-Han Zhang; Jian-Jun Zhou; Lin Li (Chemical Engineering Journal, 2025)

Supplementation with probiotics co-cultivation improves the reproductive performance in a sow-piglet model by mother-infant microbiota transmission and placental mTOR signaling - Suchen Li; Tingting Lu; Zhixin Lin; Yuanyuan Zhang; Xinchen Zhou; Meng Li; Hui Miao; Zhiren Yang; Xinyan Han (World Journal of Microbiology and Biotechnology, 2025)

Anterior and posterior cerebral white matter show different patterns of microstructural alterations in young adult smokers - Lei Jiang; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2024)

Unveiling a novel mechanism: Reduction of graphene oxide by Lysinibacillus sp. through secretion of l-ascorbic acid - Yuanyuan Zhou; Ziyi Lin; Yonghe Han; Li Gan; Ying Cheng; Zuliang Chen (Chemosphere, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

The effects of climate warming and exogenous nitrogen input on soil N2O emissions from mangroves - Weimin Song; Yan Zhao; Jian Zhou; Jianxiang Feng; Zhonglei Wang; Guangxuan Han; Elise Pendall; Guanghui Lin (Soil Biology and Biochemistry, 2024)

Response of aerobic granular sludge to salinity fluctuations in formation, stability and microbial community structures - Jie Xu; Shichang Liu; Jiazhong Zhou; Lin Li; Xuejun Bi; Wenjie Han; Di Wu (Science of The Total Environment, 2024)

Modulating charge transfer and constructing synergistic bimetallic active sites for CO-SCR reactions in inverse spinel - Qin Li; Xiaorong Han; Lin Tao; Qiuju Qin; Xuechi Du; Yuzhu Liang; Bin Li; Zhengjun Chen; Liya Zhou; Lihui Dong (Journal of Environmental Chemical Engineering, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

Interaction of Kerguelen and Amsterdam-St. Paul dual hotspots with Southeast Indian Ridge - Yiming Luo; Jian Lin; Zhiyuan Zhou; Xubo Zhang; Fan Zhang; Jinchang Zhang; Han Chen (Earth and Planetary Science Letters, 2024)

Optimizing tomato waste hydrolysate for enhanced fucoxanthin biosynthesis in mixotrophic cultivation of Isochrysis galbana - Xi-Wen Fan; Han Sun; Derek M. Ayittey; Zhi-gang Zhou; Carol Sze Ki Lin; Tao Tang; Zheng Sun (Bioresource Technology, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Drivers of denitrification and nitrification in a dryland agroecosystem: The role of abiotic and biotic factors - Zhou Fang; Zhenling Peng; Yali Zhang; Jiayao Han; Jianbin Pan; Qi Zhang; Lin Mao; Guoxi Shi; Yongjun Liu; Huyuan Feng; Xavier Le Roux (Applied Soil Ecology, 2024)

Effects of salinity and temperature on growth performance, biochemical composition, and biosilification process of Cyclotella cryptica - Yicun Zhao; Yan Sun; Zhengfeng Zhu; Yuhang Li; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Vulnerability of Global Pine Forestry's Carbon Sink to an Invasive Pathogen–Vector System - Jiao Zhou; Jingjing Du; Luís Bonifácio; Wandong Yin; Lin Huang; Jing Ning; Dongbo Han; Jiafu Hu; Wei Song; Lilin Zhao (Global Change Biology, 2024)
The substantial contribution of northern forest growth to the global increase of biomass carbon stock is well documented. However, the ecological consequences of pest‐ and disease‐related losses in these forests have not received comparable attention. This study highlights that pine species are major contributors to carbon stocks in Northern Hemisphere. The total carbon storage of Pinus in the Northern Hemisphere was estimated at 70,726 teragrams of carbon (TgC; 17.7% of the total forest carbon 478,012 TgC), accounting for 4.9%, 28.4%, and 12.5% of the total carbon storage in the forests of Asia, Europe, and North America, respectively. However, pine trees were under threat from an invasive complex involving the pine wood nematode ( Bursaphelenchus xylophilus ) and Japanese pine sawyer beetle ( Monochamus spp.). Since 1977, this complex resulted in a carbon sink deficit of 1857 TgC (18% of the carbon currently stored in Europe's live tree biomass) in northern pine ecosystems. The carbon losses attributed to B. xylophilus exceeded those caused by wildfires, which are typically regarded as the primary factor of forest disturbances. Furthermore, the contributions of environmental variables indicate that the expected northward shift in precipitation patterns will exacerbate B. xylophilus threats, endangering 78% of the boreal forests across Eurasia by 2100. Among these high‐risk areas, 62% contributed significantly to global carbon sink, and 42% was protected forests. Following the present trend, carbon losses caused by the B. xylophilus complex could exceed 39% of the total carbon storage in terrestrial ecosystems. This study provides comprehensive datasets that detail the global distribution and high‐risk habitats of pine species and B. xylophilus vector beetles in affected countries. Our findings underscore the substantial risk of carbon losses posed by B. xylophilus to northern pine forests, with potential implications for global carbon dynamics and the achievement of international goals related to “carbon peak” and “carbon neutrality.”

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Networking SiO2-Al2O3 and amines into robust and long-lasting molded sorbents for continuous CO2 capture - Tong Zhou; Zhinan Wu; Yunxia Wen; Zhengxing Dai; Shuailong Song; Han Lin; Xin Feng; Xiaohua Lu; Tuo Ji; Jiahua Zhu (Chemical Engineering Journal, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction of Cu2-xS@Zn0.5Cd0.5S S-scheme heterojunction with core-shell structure for efficient photocatalytic hydrogen production and tetracycline degradation - Zhiqiang Ai; Xiaoya Zhu; Liwei Lin; Han Li; Yanan Wang; Qian Liang; Man Zhou; Song Xu; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

Determination of 3-nitropropionic acid in sugarcane using dispersive solid-phase extraction and gas chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry - Zuolong Yu; Yu Lin; Xiujin Zhou; Yao Chen; Zhijin Yang; Chao Han; Yan Shen (Food Chemistry, 2024)

Unlocking the photothermal conversion capacity of lignin and lignin-derived materials - Yanhua Guan; Hai Liu; Ying Han; Yuanjiamei Zhou; Li Yan; Lin Dai; Chuanling Si (Chemical Engineering Journal, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Analyzing multiscale associations and couplings between integrated development and eco-environmental systems: A case study of the central plains urban agglomeration, China - Hao Wu; Zhimeng Jiang; Lianqi Zhu; Anqi Lin; Han Zhou; Luyu Cen (Applied Geography, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

An axenic strain reveals the responses of Phaeodactylum tricornutum to external organic carbon - Zhengfeng Zhu; Zhichao He; Jian Li; Chengxu Zhou; Yanrong Li; Lin Zhang; Xiaohui Li; Spiros N. Agathos; Jichang Han (Journal of Oceanology and Limnology, 2024)

Sedimentary characteristics and development model of the bedded evaporites in the Paleogene Kumugeliemu formation, Kuqa depression, Northwestern China - Liang Luo; Jingxiang Guo; Chenlin Hu; Huixi Lin; Jonathan Atuquaye Quaye; Xuewen Zhou; Bo Han (Carbonates and Evaporites, 2024)

Sedimentation history linked to global change in the alpine Damqu Wetland of the Yangtze River headwater in interior Tibetan Plateau - Qinjing Shen; Xinqi Feng; Yinjun Zhou; Penghui Lin; Yuexin Liu; Yuansen Lai; Junfeng Han; YuJiao Liu; Yixuan Wang; Shuai Zhu; Zhijing Li; Zhongping Lai (Quaternary Geochronology, 2024)

Evaluating the effect of Multi-Scale droughts on autumn phenology of global land biomes with satellite observation - Ronglei Zhou; Yangyang Liu; Xueqing Wang; Xu Chen; Gaohui Duan; Peidong Han; Ziqi Lin; Haijing Shi; Zhongming Wen (Journal of Hydrology, 2024)

Rapid removal of uranium (VI) by phosphogypsum immobilized sulfate-reducing bacteria microspheres - Xiangyu Xi; Zhilin Wang; Lin Zhou; Han Song; Ying Han; Faqin Dong; Lei Zhou (Chemical Engineering Journal, 2024)

Dynamic Response Analysis of a Subsea Rigid M-Shaped Jumper under Combined Internal and External Flows - Guangzhao Li; Wenhua Li; Shanying Lin; Fenghui Han; Xingkun Zhou (Journal of Marine Science and Engineering, 2024)
To analyze the dynamic response of a rigid M-shaped jumper subjected to combined internal and external flows, a one-way coupled fluid–structure interaction process is applied. First, CFD simulations are conducted separately for the internal and external fluid domains. The pressure histories on the inner and outer walls are exported and loaded into the finite element model using inverse distance interpolation. Then, FEA is performed to determine the dynamic response, followed by a fatigue assessment based on the obtained stress data. The displacement, acceleration, and stress distribution along the M-shaped jumper are obtained. External flow velocity dominates the displacements, while internal flow velocity dominates the vibrations and stresses. The structural response to the combined effect of internal and external flows, plus the response to gravity alone, equals the sum of the structural responses to internal flow alone and external flow alone. Fatigue damage is calculated for the bend exhibiting the most intense vibration and higher stress levels, and the locations with significant damage correspond to areas with high maximum von Mises stress. This paper aims to evaluate multiple flow fields acting simultaneously on subsea pipelines and to identify the main factors that provide valuable information for their design, monitoring, and maintenance.

Global diversity of airborne pathogenic bacteria and fungi from wastewater treatment plants - Ying Wang; Wenwen Wang; Xuezheng Yu; Zixuan Wang; Ziyu Zhou; Yunping Han; Lin Li (Water Research, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Orbital global change drove fluvial aggradation and incision in Tibetan upper Mekong river: Chronological perspectives - Yinjun Zhou; Junfeng Han; Qinjing Shen; Yantian Xu; Yaling Tao; Penghui Lin; Yuansen Lai; Yixuan Wang; Zhongping Lai (Quaternary Geochronology, 2024)

Salinity influence on adsorption of lipid molecules in clay minerals: Results from experiments and calculations - Xiao Gao; Zuozhen Han; Gang Zhou; Lin Li; Xiaowei Lyu; Yanyang Zhao; Wenjie Chen; Zhenhua Qi; Fang Liu; Qingqiang Meng; Michael Steiner; Chao Han (Journal of Environmental Chemical Engineering, 2024)

Purification, characterisation and visualisation of soybean protein hydrolysis by aspergillopepsin I from mangrove Aspergillus tubingensis - Hongli Yao; Shuangping Liu; Rui Chang; Tiantian Liu; Dongna Ma; Xiao Han; Congyu Lin; Zhilei Zhou; Jian Mao (International Biodeterioration & Biodegradation, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Occurrence and spatiotemporal distribution of natural and synthetic steroid hormones in soil, water, and sediment systems in suburban agricultural area of Guangzhou City, China - Hang Lin; Liangzhuo Zhou; Shudong Lu; Han Yang; Yongtao Li; Xingjian Yang (Journal of Hazardous Materials, 2024)

Self-assembled C-Ag hybrid nanoparticle on nanoporous GaN enabled ultra-high enhancement factor SERS sensor for sensitive thiram detection - Hongpeng Zhou; Jiaoyan Qiu; Yunhong Zhang; Yanbo Liang; Lin Han; Yu Zhang (Journal of Hazardous Materials, 2024)

Assessment and management for future habitat risks under the implementation of China's territorial spatial planning: A case study from Hainan Island - Xiaolin Zhang; Xiaobin Jin; Xinyuan Liang; Xu Shi; Rui Sun; Wenjie Zhu; Jinhuang Lin; Bo Han; Yinkang Zhou (Environmental Impact Assessment Review, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Four new compounds from the fruits of Chinese dwarf cherry ( Prunus humilis Bunge) - Sheng Dong; Ying Zhou; Ji-Chao Wang; Yi-Lin Zhuo; Yi-Han Sun; Jun-Gang Wang; Guo-Gang Zhang (Natural Product Research, 2024)

Flow pattern evolution and flow-induced vibration response in multiphase flow within an M-shaped subsea jumper - Wenrui Song; Wenhua Li; Shanying Lin; Xingkun Zhou; Fenghui Han (Ocean Engineering, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

Simultaneous determination of seawater trimethylamine and methanol by purge and trap gas chromatography using dual nitrogen-phosphorus detector and flame-ionization detector - Fei Jiang; Zhen Zhou; Jin-Yan Wang; Wen-Jia Guan; Lei-Gang Han; Xian-Biao Lin; Guang-Chao Zhuang (Frontiers in Marine Science, 2024)
Compounds containing one carbon atom or no carbon-carbon bond (C1 compounds), such as trimethylamine and methanol, are important climate relevant gases in the atmosphere and play key roles in global warming. The ocean is a significant source or sink of such compounds, while the concentrations of trimethylamine and methanol in seawater remain largely unconstrained due to the analytical challenges involved. Therefore, it is necessary to establish a continuous, rapid and sensitive method for the determination of these compounds with high polarity, volatility or solubility at low seawater concentrations. Here we developed a purge and trap system, coupled to a gas chromatography equipped with dual nitrogen phosphorus detector (NPD) and flame ionization detector (FID) for the simultaneous online analysis of trimethylamine and methanol at nanomolar range using a small sample volume (~ 10 mL). The dual detection of trimethylamine and methanol with NPD or FID was achieved by installing a capillary flow splitter between the capillary column and detectors. After modification and optimization of the setup and conditions, excellent linearity (R 2 > 0.99) and repeatability (< 6%) were obtained for both compounds; the detection limits for trimethylamine and methanol were 0.3 nM and 17.6 nM, respectively. Using this method, water samples collected from coastal and open ocean were analyzed; trimethylamine and methanol concentrations ranged from 0.6 to 18.8 nM and 26.0 to 256.2 nM, respectively. Collectively, this method allowed for online, rapid, sensitive and simultaneous quantification of trace trimethylamine and methanol concentrations with low-cost instrumentation and small sample volume, which makes it promising for further application in volatile compounds analysis in marine environments.

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

Long-term conservation tillage enhances microbial carbon use efficiency by altering multitrophic interactions in soil - Ling Ma; Guixiang Zhou; Jiabao Zhang; Zhongjun Jia; Hongtao Zou; Lin Chen; Congzhi Zhang; Donghao Ma; Changdong Han; Yan Duan (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

In vitro assessment of the bacterial stress response and resistance evolution during multidrug-resistant bacterial invasion of the Xenopus tropicalis intestinal tract under typical stresses - Xiaojun Lin; Ruiqi Han; Taojie Liang; Chaonan Zhang; Yanbin Xu; Huishi Peng; Xiao Zhou; Lu Huang (Journal of Hazardous Materials, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

Soil properties and fungal community jointly explain N2O emissions following N and P enrichment in an alpine meadow - Zhenrong Lin; Lina Shi; Xiaoting Wei; Bing Han; Cuoji Peng; Zeying Yao; Yicheng He; Qing Xiao; Xinmin Lu; Yanfang Deng; Huakun Zhou; Kesi Liu; et al. (Environmental Pollution, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

An Improved VO Method for Collision Avoidance of Ships in Open Sea - Mao Zheng; Kehao Zhang; Bing Han; Bowen Lin; Haiming Zhou; Shigan Ding; Tianyue Zou; Yougui Yang (Journal of Marine Science and Engineering, 2024)
In order to effectively deal with collisions in various encounter situations in open water environments, a ship collision avoidance model was established, and multiple constraints were introduced into the velocity obstacle method, a method to determine the ship domain by calculating the safe distance of approach was proposed. At the same time, the ship collision avoidance model based on the ship domain is analyzed, and the relative velocity set of the collision cone is obtained by solving the common tangent line within the ellipse. The timing of starting collision avoidance is determined by calculating the ship collision risk, and a method for ending collision avoidance is proposed. Finally, by comparing the simulation experiments of the improved algorithm with those of the traditional algorithm and the actual ship experiment results of manual ship maneuvering, it is shown that the method can effectively avoid collisions based on safe encounter distances that comply with navigation experience in different encounter situations. At the same time, it has better performance in collision avoidance behavior. It has certain feasibility and practical applicability.

Prediction of thermal conductivities of insulation materials under water immersion and freeze–thaw conditions for tunnels in cold regions - Fenglei Han; Zonghan Liu; Jiazheng Li; Wenbing Yu; Qixiang Yan; Yuanfu Zhou; Shuzhen Zhang; Lin Chen (Tunnelling and Underground Space Technology, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Long-term fertilization affects microbial necromass accumulation by regulating nutrient and enzymatic stoichiometry in a calcareous Fluvisol - Changdong Han; Lin Chen; Xiuli Xin; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Yue Li; Ling Ma; Jiabao Zhang (Applied Soil Ecology, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Effects of dietary glutamine supplementation on growth performance, intestinal digestive ability, antioxidant status and hepatic lipid accumulation in Xenocypris davidi (Bleeker,1871) - Yuehan Wang; Zuxiang Peng; Lin Yan; Xin Gao; Lin Wu; Shuchang Cui; Mengyuan Zhou; Tongjun Ren; Wei Wang; Shuhao Sun; Yuzhe Han; Hang Sun (Aquaculture International, 2024)

PSO-Based Predictive PID-Backstepping Controller Design for the Course-Keeping of Ships - Bowen Lin; Mao Zheng; Bing Han; Xiumin Chu; Mingyang Zhang; Haiming Zhou; Shigan Ding; Hao Wu; Kehao Zhang (Journal of Marine Science and Engineering, 2024)
Ship course-keeping control is of great significance to both navigation efficiency and safety. Nevertheless, the complex navigational conditions, unknown time-varying environmental disturbances, and complex dynamic characteristics of ships pose great difficulties for ship course-keeping. Thus, a PSO-based predictive PID-backstepping (P-PB) controller is proposed in this paper to realize the efficient and rapid course-keeping of ships. The proposed controller takes the ship’s target course, current course, yawing speed, as well as predictive motion parameters into consideration. In the design of the proposed controller, the PID controller is improved by introducing predictive control. Then, the improved controller is combined with a backstepping controller to balance the efficiency and stability of the control. Subsequently, the parameters in the proposed course-keeping controller are optimized by utilizing Particle Swarm Optimization (PSO), which can adaptively adjust the value of parameters in various scenarios, and thus further increase its efficiency. Finally, the improved controller is validated by carrying out simulation tests in various scenarios. The results show that it improves the course-keeping error and time-response specification by 4.19% and 9.71% on average, respectively, which can efficiently achieve the course-keeping of ships under various scenarios.

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Water stress significantly affects the diurnal variation of solar-induced chlorophyll fluorescence (SIF): A case study for winter wheat - Jingyu Lin; Litao Zhou; Jianjun Wu; Xinyi Han; Bingyu Zhao; Meng Chen; Leizhen Liu (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

High-performance petal-like nickel organic framework for efficient dye sequestration - Frank Peprah Addai; Yuelin Liu; Jiacong Wu; Xinnan Ma; Juan Han; Feng Lin; Fengcheng Xue; Yang Zhou; Yun Wang (Journal of Water Process Engineering, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Eupatilin inhibits xanthine oxidase in vitro and attenuates hyperuricemia and renal injury in vivo - Guitao Xu; Lele Wu; Hongxuan Yang; Tianfeng Liu; Ying Tong; Jiliang Wan; Bin Han; Lin Zhou; Xuguang Hu (Food and Chemical Toxicology, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Observed oceanic response to Tropical Cyclone Amphan (2020) from a subsurface mooring in the Bay of Bengal - Yingyu Peng; Di Tian; Feng Zhou; Han Zhang; Xiao Ma; Dingyong Zeng; Qicheng Meng; Beifeng Zhou; Ruijie Ye; Yeqing Chen; Feilong Lin; Zhentao Hu; et al. (Progress in Oceanography, 2023)

The behavior of whey protein isolate-curcumin complex at the oil-water interface - Huanqing Lei; Jiawei Lin; Zeling Chen; Zenan Shi; Debao Niu; Xinan Zeng; Lin Zhou; Zhong Han (Food Hydrocolloids, 2023)

Covalent organic frameworks for modulating crystallization kinetics in perovskite photovoltaics - Xiao Liang; Chaoqin Han; Fei Wang; Jiajun Wu; Xianfang Zhou; Haoran Lin; Xiaoyuan Liu; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Synergistic effect between electric field and Ce-doped catalysts to promote hydrogen production from ammonia decomposition - Xiaochao Wang; Zijian Zhang; Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Dong Han; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Black soldier fly pulp in the diet of golden pompano: Effect on growth performance, liver antioxidant and intestinal health - Zuzhe Li; Chengzong Han; Zhanzhan Wang; Zhenyu Li; Leshan Ruan; Heizhao Lin; Chuanpeng Zhou (Fish & Shellfish Immunology, 2023)

Experimental investigation and one-way coupled fluid-structure interaction analysis of gas-liquid two-phase flow conveyed by a subsea rigid M-shaped jumper - Guangzhao Li; Wenhua Li; Fenghui Han; Shanying Lin; Xingkun Zhou (Ocean Engineering, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Effects of filter cartridge wetted before filtration and during filtration on the performance of cartridge dust collector - Shihang Li; Liyuan Liu; Xiaoyu Tan; Hao Liu; Changgeng Gui; Xingyue Chen; Muze Han; Yihan Lin; Jiang Shao; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Marine fungus-derived alkaloid inhibits the growth and metastasis of gastric cancer via targeting mTORC1 signaling pathway - Shuai Ma; Yiwei Hu; Jianjiao Chen; Xiaojuan Wang; Chenxi Zhang; Qianqian Liu; Guodi Cai; Hong Wang; Jianwei Zheng; Qianqian Wang; Lin Zhong; Bin Yang; et al. (Chemico-Biological Interactions, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Cabernet sauvignon dry red wine ameliorates atherosclerosis in mice by regulating inflammation and endothelial function, activating AMPK phosphorylation, and modulating gut microbiota - Xinlong Cheng; Xue Han; Liangfu Zhou; Yasai Sun; Qian Zhou; Xuan Lin; Zhe Gao; Jie Wang; Wen Zhao (Food Research International, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

The role of harmonized Landsat Sentinel-2 (HLS) products to reveal multiple trajectories and determinants of cropland abandonment in subtropical mountainous areas - Changqiao Hong; Alexander V. Prishchepov; Xiaobin Jin; Bo Han; Jinhuang Lin; Jingping Liu; Jie Ren; Yinkang Zhou (Journal of Environmental Management, 2023)

Arsenic triggered nano-sized uranyl arsenate precipitation on the surface of Kocuria rosea - Lei Zhou; Faqin Dong; Xiangyu Xi; Lin Zhou; Qunwei Dai; Mingxue Liu; Ying Han; Gang Yang; Yongde Zhang (Journal of Environmental Radioactivity, 2023)

Using Pgst-4::GFP-transformed Caenorhabditis elegans for drinking water quality monitoring - Yan Wang; Xue Han; Jie Zhang; Meng-Xuan Zhou; Ai-Lin Liu (Environmental Monitoring and Assessment, 2023)

Response mechanisms of Chlorella sorokiniana to microplastics and PFOA stress: Photosynthesis, oxidative stress, extracellular polymeric substances and antioxidant system - Zhilin Zhao; Xiaoying Zheng; Zongshuo Han; Shanshan Yang; Huijie Zhang; Tao Lin; Chao Zhou (Chemosphere, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Morphological and physicochemical characteristics, biological functions, and biomedical applications of diatom frustule - Chenfei Yang; Chao Feng; Yuhang Li; Zheng Cao; Yan Sun; Xiaohui Li; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Characterization of procyanidin extracts from hawthorn (Crataegus pinnatifida) in human colorectal adenocarcinoma cell line Caco-2, simulated Digestion, and fermentation identified unique and novel prebiotic properties - Xue Han; Qian Zhou; Zhe Gao; Guanying Bianca Xu; Hong Chen; Bimal Chitrakar; Yasai Sun; Wen Zhao; Xuan Lin; Kaixuan Zhou; Zhisheng Zhang (Food Research International, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

Transcriptome profiling reveals the roles of pigment formation mechanisms in yellow Paeonia delavayi flowers - Hongzhu Zou; Lin Zhou; Lulu Han; JiHang Lv; YingHua Jia; Yan Wang (Molecular Genetics and Genomics, 2023)
The yellow colour of ornamental varieties of tree peony originated from Paeonia delavayi . However, but P. delavayi and Paeonia suffruticosa belong to different subgroups, so hybridization is difficult and results in a long breeding cycle. However, no comprehensive transcriptomic profiling has focused on the colour formation mechanisms of yellow tree peony petals. Analysing the colour formation mechanism of yellow petals in P. delavayi is very important for directional molecular breeding. In this study, the transcriptional map of yellow pigment development in petals was used to analyse the mechanism of petal colour formation. We analysed the genes related to the metabolism of flavonoids and carotenoids and the transcription factors (TFs) involved in P. delavayi var. lutea (pure yellow individual) yellow pigment development using transcriptome sequence profiling. Transcriptome sequence profiles revealed three and four differentially expressed transcripts (DETs) involved in flavonoid biosynthesis and carotenoid biosynthesis, respectively. An analysis of DETs in the flavonoid pathway showed that chalcone synthase ( CHS ) and chalcone 2´-glucosyltransferases (THC 2’GT ) act in synergy to synthesize isosalipurposide (ISP). CHS and flavonol synthase ( FLS ) synergistically synthesize quercetin and kaempferol. DEG analysis of the carotenoid pathway revealed that phytoene synthase ( PSY ), carotenoid isomerase ( CRTISO ) and β-carotene hydroxylases ( CHYB ) play a key role in regulating lutein formation, and carotenoid cleavage dioxygenase ( CCD ) plays an important role in the degradation of carotenoids. These two pathways may be regulated by TF families such as bHLH , ARF , and MYB . The results of the transient overexpression of genes showed that CHS and CHI are regulated by PdMYB2 . In this study, the molecular mechanism of ISP synthesis was analysed in depth, and the complete metabolic pathway of carotenoids in Paeonia L. was reported for the first time. By studying the formation mechanism of yellow pigment in P. delavayi petals, a breeding strategy for improving flavonol and carotenoid contents and reducing anthocyanin synthesis by genetic engineering was suggested.

Tolerance and recovery of aerobic granular sludge: Impact of perfluorooctanoic acid - Xiaoying Zheng; Huijie Zhang; Zhi Xu; Tao Lin; Shanshan Yang; Zhilin Zhao; Zongshuo Han; Chao Zhou (Chemosphere, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Enrofloxacin exposure induces anxiety-like behavioral responses in zebrafish by affecting the microbiota-gut-brain axis - Dandan Tian; Wei Shi; Yihan Yu; Weishang Zhou; Yu Tang; Weixia Zhang; Lin Huang; Yu Han; Guangxu Liu (Science of The Total Environment, 2023)

Evaluating the human use efficiency of urban built environment and their coordinated development in a spatially refined manner - Yi Bao; Zhou Huang; Linna Li; Han Wang; Jiayuan Lin; Gang Liu (Resources, Conservation and Recycling, 2023)

Newly isolated halotolerant Aspergillus sp. showed high diesel degradation efficiency under high salinity environment aided with hematite - Sumbal Sajid; Víctor Resco de Dios; Obey Kudakwashe Zveushe; Farhan Nabi; Songrong Shen; Qianlin Kang; Lei Zhou; Lin Ma; Wei Zhang; Yulian Zhao; Ying Han; Faqin Dong (Journal of Hazardous Materials, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

High PCBs mineralization capability of a resuscitated strain Bacillus sp. LS1 and its survival in PCB-contaminated soil - Zhen Han; Qihua Lin; Shusheng Zhang; Xinru Zhou; Si Li; Faqian Sun; Chaofeng Shen; Xiaomei Su (Science of The Total Environment, 2023)

Variation of microplastics and biofilm community characteristics along the long-distance raw water pipeline - Hui Tao; Lingqin Zhou; Yiting Qi; Yiyang Chen; Zongshuo han; Tao Lin (Process Safety and Environmental Protection, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

Hypoxia-induced ROS aggravate tumor progression through HIF-1α-SERPINE1 signaling in glioblastoma - Lin Zhang; Yuanyuan Cao; Xiaoxiao Guo; Xiaoyu Wang; Xiao Han; Kouminin Kanwore; Xiaoliang Hong; Han Zhou; Dianshuai Gao (Journal of Zhejiang University-SCIENCE B, 2023)

Feasibility Study of a Novel Open Ocean Aquaculture Ship Integrating with a Wind Turbine and an Internal Turret Mooring System - Hanyu Liu; Mingsheng Chen; Zhaolong Han; Hao Zhou; Lin Li (Journal of Marine Science and Engineering, 2022)
Marine aquaculture has been expanded into more remote areas due to the increasing demand for high value-added fish products, bringing more challenges in fuel supply and mooring safety to open ocean aquaculture farms. Therefore, the idea of integrating aquaculture farms with offshore renewable energy has attracted tremendous interest. This study proposes a novel open ocean aquaculture ship integrated with a NREL 5 MW wind turbine. In addition, an internal turret mooring system is installed at the bow of the aquaculture ship, making the wind turbine always face the wind blowing direction due to the weathervaning effect. In this study, a preliminary study of the dynamics and wind power generation of the proposed open ocean aquaculture ship was conducted. The aerodynamic and elastic effects of the wind turbine and the effect of nets under the wave and current behavior on the dynamics of the single-point moored aquaculture ship were investigated. Furthermore, the effects of the dynamics of the aquaculture ship on the power generation of the wind turbine were also studied to investigate the feasibility of the idea to integrate an aquaculture ship with a wind turbine.

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

Nutrient distributions and nitrogen-anomaly (N*) in the tropical North Pacific Ocean - Aiqin Han; Yu Wang; Yunlong Huo; Cai Lin; Kaiwen Zhou; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Transcriptome and metabolome profiling of interspecific CSSLs reveals general and specific mechanisms of drought resistance in cotton - Bei Han; Fengjiao Wang; Zhilin Liu; Lin Chen; Dandan Yue; Weinan Sun; Zhongxu Lin; Xianlong Zhang; Xiaofeng Zhou; Xiyan Yang (Theoretical and Applied Genetics, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Reciprocal modulation between cigarette smoking and internet gaming disorder on participation coefficient within functional brain networks - Xianxin Qiu; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Hao Lei; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2022)

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

Video target detection of East Asian migratory locust based on the MOG2-YOLOv4 network - Zhao Bai; Zhan Tang; Lei Diao; Shuhan Lu; Xuchao Guo; Han Zhou; Chengqi Liu; Lin li (International Journal of Tropical Insect Science, 2022)

Synthesis of Silver- and Strontium-Substituted Hydroxyapatite with Combined Osteogenic and Antibacterial Activities - Yunfei Li; Wenying Wang; Jing Han; Zirui Li; Qiuxiang Wang; Xue Lin; Kun Ge; Guoqiang Zhou (Biological Trace Element Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Effects of diethyl aminoethyl hexanoate on the physiology and selenium absorption of grape seedlings - Lei Liu; Jiaxi Han; Lili Deng; Huixuan Zhou; Yuhui Bie; Qianhe Jing; Lijin Lin; Jin Wang; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Identification of potential sex-related genes in Siniperca chuatsi - Qiaoying Zhu; Chong Han; Cheng Peng; Xingni Zhou; Chongwei Wang; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Journal of Oceanology and Limnology, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Sex-specific effects of cigarette smoking on caudate and amygdala volume and resting-state functional connectivity - Fuchun Lin; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Hao Lei (Brain Imaging and Behavior, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

DNA methylation of JAK3/STAT5/PPARγ regulated the changes of lipid levels induced by di (2-ethylhexyl) phthalate and high-fat diet in adolescent rats - Qi Xu; Wen Qi; Yuezhu Zhang; Qi Wang; Shuang Ding; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Correction to: Effects of di (2-ethylhexyl) phthalate and high-fat diet on lipid metabolism in rats by JAK2/STAT5 - Yuezhu Zhang; Liting Zhou; Zhaoming Zhang; Qi Xu; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Lin Ye (Environmental Science and Pollution Research, 2020)

Effects of di (2-ethylhexyl) phthalate and high-fat diet on lipid metabolism in rats by JAK2/STAT5 - Yuezhu Zhang; Liting Zhou; Zhaoming Zhang; Qi Xu; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Lin Ye (Environmental Science and Pollution Research, 2020)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Sex differences in resting-state cerebral activity alterations in internet gaming disorder - Yawen Sun; Yao Wang; Xu Han; Wenqing Jiang; Weina Ding; Mengqiu Cao; Yasong Du; Fuchun Lin; Jianrong Xu; Yan Zhou (Brain Imaging and Behavior, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

QTL mapping for maize starch content and candidate gene prediction combined with co-expression network analysis - Feng Lin; Ling Zhou; Bing He; Xiaolin Zhang; Huixue Dai; Yiliang Qian; Long Ruan; Han Zhao (Theoretical and Applied Genetics, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Genetic Diversity and Population Structure of Coffee Germplasm Collections in China Revealed by ISSR Markers - Lin Yan; Collins Ogutu; Lifang Huang; Xiaoyang Wang; Hua Zhou; Yulan Lv; Yuzhou Long; Yunping Dong; Yuepeng Han (Plant Molecular Biology Reporter, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Dual therapy with clopidogrel and aspirin prevents early neurological deterioration in ischemic stroke patients carrying CYP2C19*2 reduced-function alleles - Jing Lin; Zhao Han; Chun Wang; Xingyang Yi; Zhenxiao Chai; Qiang Zhou; Ruyue Huang (European Journal of Clinical Pharmacology, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Structural predication and antigenic analysis of Toxoplasma gondii ROP20 - Jian Zhou; Wanchun Wang; Pengxia Song; Lin Wang; Yali Han; Jingjing Guo; Zhen Hao; Xi Zhu; Qiong Zhou; Xiadong Du; Gang Lu; Shenyi He; et al. (Acta Parasitologica, 2018)
Toxoplasma gondii infects almost all the warm-blooded animals. ROP20 protein is expressed in the rhoptry of Toxoplasma gondii . In this study, the secondary structure of ROP20 was analyzed using SMART software. We constructed and analyzed the 3D model of ROP20 protein using SWISS-MODEL online procedure and Visual Molecular Dynamics (VMD) software. The structure analysis fully indicated that ROP20 protein is an important member of the ROP family. Furthermore, We used DNASTAR software and Epitope Database online service to analyze liner-B cell epitopes and T-cell epitopes of ROP20 protein. All the analysis results of ROP20 protein can provide positive information on treatment and vaccine for toxoplasmosis. Moreover, ROP20 gene was obtained from PCR, and a recombinant eukaryotic expression vector (pEGFP-C1-ROP20) was constructed in the following study. After restriction enzyme digestion, the constructed plasmid was transfected into HEK 293-T cells. The RT-PCR result indicated that the recombinant plasmid could transcribe successfully in HEK 293-T cell. The results of western blotting indicated the expressed proteins can be recognized by anti-STAg mouse sera.

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock - Feng Yao; Yuan-qiang Lu; Jiu-kun Jiang; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2017)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Relation of Transcriptional Factors to the Expression and Activity of Cytochrome P450 and UDP-Glucuronosyltransferases 1A in Human Liver: Co-Expression Network Analysis - Shilong Zhong; Weichao Han; Chuqi Hou; Junjin Liu; Lili Wu; Menghua Liu; Zhi Liang; Haoming Lin; Lili Zhou; Shuwen Liu; Lan Tang (The AAPS Journal, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Impact of heat waves on nonaccidental deaths in Jinan, China, and associated risk factors - Jun Zhang; Shouqin Liu; Jing Han; Lin Zhou; Yueling Liu; Liu Yang; Ji Zhang; Ying Zhang (International Journal of Biometeorology, 2016)

BM-MSCs and Bio-Oss complexes enhanced new bone formation during maxillary sinus floor augmentation by promoting differentiation of BM-MSCs - Qian Zhou; Bo-Han Yu; Wei-Cai Liu; Zuo-Lin Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Seroprevalence and molecular detection of Mycoplasma ovipneumoniae in goats in tropical China - Guang Rong; Jun-Ming Zhao; Guan-Yu Hou; Han-Lin Zhou (Tropical Animal Health and Production, 2014)

Antidepressant-like effects of the phosphodiesterase-4 inhibitor etazolate and phosphodiesterase-5 inhibitor sildenafil via cyclic AMP or cyclic GMP signaling in mice - Chuang Wang; Jianrui Zhang; Yang Lu; Peipei Lin; Tonghe Pan; Xin Zhao; Aiming Liu; Qinwen Wang; Wenhua Zhou; Han-Ting Zhang (Metabolic Brain Disease, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Precipitation of calcite induced by Synechocystis sp. PCC6803 - Zuozhen Han; Huaxiao Yan; Shixue Zhou; Hui Zhao; Yan Zhang; Ningning Zhang; Chuankai Yao; Lin Zhao; Chunyan Han (World Journal of Microbiology and Biotechnology, 2013)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Overexpression of the Arabidopsis photorespiratory pathway gene, serine: glyoxylate aminotransferase (AtAGT1), leads to salt stress tolerance in transgenic duckweed (Lemna minor) - Lin Yang; Huajun Han; Miaomiao Liu; Zhaojiang Zuo; Kaiqiang Zhou; Jianchao Lü; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

High angle prestack depth migration with absorption compensation - Hui Zhou; He Lin; Shan-Bo Sheng; Han-Ming Chen; Ying Wang (Applied Geophysics, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl - Zao-Fa Jiang; Su-Zhen Huang; Yu-Lin Han; Jiu-Zhou Zhao; Jia-Jia Fu (Ecotoxicology, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Biomass and carbon dynamics of a tropical mountain rain forest in China - DeXiang Chen; YiDe Li; HePing Liu; Han Xu; WenFa Xiao; TuShou Luo; Zhang Zhou; MingXian Lin (Science China Life Sciences, 2010)

Genetic analysis of ABCG2 gene C421A polymorphism with gout disease in Chinese Han male population - Binbin Wang; Zhimin Miao; Shiguo Liu; Jing Wang; Shiyi Zhou; Lin Han; Dongmei Meng; Yunlong Wang; Changgui Li; Xu Ma (Human Genetics, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)